Dearomative logic in natural product total synthesis. Issue 12 (29th September 2022) - Huck, Christopher J.; Boyko, Yaroslav D.; Sarlah, David
Abstract : This review explores the strategies and tactics of effective dearomative retrosynthetic logic, illustrated through numerous outstanding examples of contemporary natural product total synthesis. Abstract : Covering: 2011 to 2022 The natural world is a prolific source of some of the most interesting, rare, and complex molecules known, harnessing sophisticated biosynthetic machinery evolved over billions of years for their production. Many of these natural products represent high-value targets of total synthesis, either for their desirable biological activities or for their beautiful structures outright; yet, the high sp 3 -character often present in nature's molecules imparts significant topological complexity that pushes the limits of contemporary synthetic technology. Dearomatization is a foundational strategy for generating such intricacy from simple materials that has undergone considerable maturation in recent years. This review highlights the recent achievements in the field of dearomative methodology, with a focus on natural product total synthesis and retrosynthetic analysis. Disconnection guidelines and a three-phase dearomative logic are described, and a spotlight is given to nature's use of dearomatization in the biosynthesis of various classes of natural products. Synthetic studies from 2011 to 2021 are reviewed, and 425 references are cited.